PENGARUH PADAT TEBAR UNTUK MENINGKATKAN PRODUKTIVITAS BUDIDAYA IKAN NILEM (Osteochilus hasseltii) DENGAN PENGGUNAAN BATU AERASI HIGH OXY - Heti Herawati; Rini Yulianti; Zahidah Zahidah; Asep Sahidin (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
Conventional fish cultivation system for nilem fish which is currently mostly done with high density of stocking in order to produce high production as well. This will of course have an impact on the availability of dissolved oxygen in aquaculture ponds that will result in decreased production. The use of high oxy aeration stone can increase the dissolved oxygen level in the conventional fish farming cultivation system so that the productivity of fish nilem will increase also with the reduction of mortality rate of the nilem fish. This study aims to determine the extent of the effect of adding high oxy aeration rock to increase dissolved oxygen levels that can support the success and productivity in conventional fish farming system nilem. The research was conducted in the Physiology Laboratory of Animal Water of FPIK Unpad with experimental method of Completely Random Design with three treatments: fish density of 100, 200 and 300 head / m2 and four replications. The results obtained 200 treatment / m2 gives the best results shown from the growth rate of daily weight and the highest survival during the study of 2.7% and 75.4%.